Vectors of socio-economic development in Russia. Modern challenges and opportunities - Danilchenko S. L., Shemet V. S., Minakov A. V., Ivanova L. N., Kugai A. I., Malashenko I. V., Kruglov V. N., Alekseeva N. A., Abasheva O. I., Konina E. A., Abasheva O. V., Doronina S. A., Kostenko E. G., Sal'nikova N. A., Kurdiumov A. V., Shaibakova L. F. (Vectors of socio-economic development in Russia. Modern challenges and opportunities, 2025)
the relevance of the research topic lies in the need for continuous improvement of the management system of state-owned enterprises based on the analysis of estimated performance indicators and identification of existing problems. The object of the study is the state unitary enterprise of the subjects of the Russian Federation of the Kaluga Region Kaluga MTS (hereinafter abbreviated as MTS). SE KO «Kaluga MTS»). The subject of the research is the management system of the Kaluga MTS State Enterprise. The theoretical basis of the research was domestic and foreign scientific periodicals, textbooks, and materials from scientific and practical conferences and monographs. The information base was the official website of the enterprise, its financial statements and reports of the Ministry of Agriculture of the Kaluga region. During the preparation of the material, such methods as computational-analytical, structural-logical, monographic, as well as methods of analysis and synthesis were used.
Keywords: интеллектуальная собственность; система управления; management system; экономический эффект; мотивация труда; лизинг; leasing; intellectual property; labor motivation; economic effect; индикативный подход; agricultural sector; государственное предприятие; сельскохозяйственная сфера; эффект синергии; мультипликативный подход; state-owned enterprise; indicative approach; synergy effect; multiplicative approach